A Novel Traffic Surveillance System Using an Uncalibrated Camera. (23rd February 2022) - Gupta, Sandeep; Kartha, Ranju S; Ramirez-Asis, Edwin; Flores-Albornoz, Judith; Vílchez-Vásquez, Rosa; Singh, Sitesh Kumar
Abstract : The objective of this paper is to present an effective and reliable method for the traffic surveillance using the concepts of digital image processing. The paper proposes a system that can detect, track, and estimate velocity of vehicles using an uncalibrated camera and also detect and recognize their registration number plate. This approach provides a cost-effective alternative for traffic flow monitoring and surveillance. This robust system finds its applications in urban traffic management systems, military installation, and research facility security systems. This approach is a computationally efficient approach for detecting and tracking moving cars on the road utilizing uncalibrated cameras mounted on the road. It is also helpful for military installation because all the security issues have been detected by using this approach.